Indonesian Labor Reform Since 1998 - Uwiyono, Aloysius (UI Scholars Hub, 2008)
The development of labor law in the world essentially influenced by the newest models in industrial relations in each county. In general, there are two models, Corporatist Model/Regulatory Model and Contractual Model. The first model frequently meets in the countries whose use the civil law like France, Netherlands, Germany, and Indonesia, while the second model frequently meet in common law countries like the United States of America’s, England, Australia, and Malaysia. Based on the two theories above, this article will discuss how the development of the reformation of labor law in Indonesia especially since the reformatioan in 1998.